Population Structure Analysis of Javan Rhinoceros at Ujung Kulon National Park, West Java - Widya Pintaka Bayu Putra; Mochamad Syamsudin; Asep Yayus Firdaus (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2020)
Javan rhino (Rhinoceros sondaicus) is one of the rare animals with critically endangered status. The Ujung Kulon National Park (UKNP) is one of javan rhino habitat in Indonesia. Every year the monitoring program for javan rhino in UKNP was performed to identify the animals. This research was aimed to analyze the population structure of javan rhino based on the records data from 2011 to 2019 in UKNP. Research showed that the natural increase (NI) and birth rate (BR) values were 17.34% (moderate) and 67.33% (high) respectively. The net return rate (NRR) value was 15.38% (male) and 14.28% (female). The NRR value in the present study was lower than 100% and caused by less number of animals in a population for 30 years of breeding length. Despite this, the inbreeding rate of javan rhino at UKNP in 2019 was 0.01 (low). It was concluded that the natural increase of javan rhino at UKNP showed a good parameter but the population number needs to be increased.